PENGARUH PEMBIASAAN KEAGAMAAN TERHADAP AKHLAK SISWA KELAS 8 DI SMP NEGERI 1 SAWAHAN NGANJUK - Abdul Rouf; Adibah Adibah (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2024)
This study aims to determine the Influence of Religious Habits on the Morals of 8th Grade Students at SMP Negeri 1 Sawahan Nganjuk. This study uses a quantitative approach, because the data obtained is presented in the form of numbers and analysis based on statistics. The data that will be presented in the form of numbers in this study are religious habits and moral data taken from the research object. While the data collection methods used in this study are: Observation method, Documentation method and Questionnaire method. Data analysis techniques in this study include descriptive statistical analysis, inferential analysis, and hypothesis testing. The results of this study indicate that: religious habits have an influence on the morals of 8th grade students at SMP Negeri 1 Sawahan Nganjuk with a correlation coefficient of 0.602. This means that religious habits carried out by 8th grade students have a high influence on their morals. The coefficient of determination value in SPSS v.25 data processing is 0.355.